Impact of Street Photography on Social Awareness in Nairobi, Kenya - Udo Kariuki; Etenesh Okafor; Olalekan Abioye (Art and Society, 2024)
This research explores the multifaceted realm of street photography in the dynamic urban context of Nairobi, Kenya. Focusing on the potential of this visual medium for social change, the study delves into the ethical considerations, cultural sensitivities, and societal impact associated with street photography. It investigates the role of street photographers as storytellers and their influence on public discourse, aiming to shed light on pressing social issues and challenge ingrained perspectives. The guidelines proposed for responsible street photography offer a comprehensive framework, emphasizing informed consent, cultural sensitivity, collaboration, social impact assessment, and educational initiatives. Through these guidelines, the research envisions a future where street photography becomes a catalyst for positive societal transformation within Nairobi’s diverse and evolving landscape.